“The impacts of redesigning the work practice using IT on the employee’s performance in Citibank, N.A. Bangladesh - Islam, Nusrat (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.